ANALISIS KINERJA REKSA DANA SAHAM SELAMA MASA PANDEMI COVID-19 DI INDONESIA - Ningrum, Retno Widya; Irfan Achmad Musadat, Irfan Achmad Musadat; Agung Pramayuda, Agung Pramayuda (Fakultas Keguruan Dan Ilmu Pendidikan Universitas Pasundan, 2024)
The Covid-19 pandemic period in Indonesia lasts from 31 March 2020 to 21 June 2023 in accordance with the Decree of the President of the Republic of Indonesia. Indirectly, this also affects returns from stock mutual funds, both conventional and equity. During the Covid-19 pandemic, the JCI produced higher returns compared to the Stock Mutual Fund Index with quite a large difference in figures. IHSG produced a return of 51.83% while the Stock Mutual Fund Index only produced a return of 29.73%. As an investor or potential stock mutual fund investor, this is an interesting concern because a good investment should be able to exceed the benchmark return. However, to comprehensively assess the performance of an investment, apart from looking at the returns generated, it is also necessary to consider the risks contained in the investment instrument. Unfortunately, there are still many investors and prospective mutual fund investors who still do not understand how to assess their investment performance. There are several methods for assessing investments in portfolio form, including Sharpe Ratio, Treynor Ratio, Jensen's Alpha and Information Ratio. This research aims to provide an overview of the mutual fund performance assessment process and analysis of this assessment. Meanwhile, the focus of this research is the performance of stock mutual funds during the Covid-19 pandemic in accordance with the Decree of the President of the Republic of Indonesia. The conclusions of this research are as follows: In March - December 2020, it was discovered that Ashmore Dana Progresif Nusantara received the highest performance score using two methods, namely Sharpe ratio and Information ratio. In 2021, TRIM Bhakti Bangsa received the highest performance score using two methods, namely Jensen Alpha and Information ratio. In 2022, Bahana Primavera 99 Class S received the highest performance score with three, namely Treynor ratio, Jensen Alpha and Information ratio. In January – June 2023, Syailendra Dana Ekuitas Sejahtera received the highest performance score using two methods, namely Jensen Alpha and Information ratio. However, if you look at the mutual fund that received the highest performance scores during the Covid-19 pandemic, it was Schroder Dana Prestasi Prima.